Síndrome nefrótica congênita secundária à infecção congênita: um relato de caso - Camila Maria Florencio Santos; Gabriella Aguiar Santos Faria; Marianne Fernanda de Melo Duarte; Filipe Marinho Pinheiro da Camara; Tereza Rebecca de Melo e Lima (Sociedade Brasileira de Pediatria, 2023)
Congenital nephrotic syndrome (CNS) is a rare glomerular disease characterized by massive proteinuria, hypoproteinemia, and generalized edema that manifests in the first 3 months of life. This report describes the case of a patient with congenital nephrotic syndrome secondary to congenital infection in a pediatric patient. The article aims to sensitize pediatricians to the pathology and its etiologies, considering that clinical suspicion allows for better therapeutic management of affected patients and the prevention of potential sequelae.